Advances of DNA computing in cryptography - Namasudra, Suyel, editor; Deka, Ganesh Chandra, 1969- editor (Boca Raton : CRC Press, 2019)
"This book discusses the current technologies of cryptography using DNA computing. It provides a judicious mix of concepts, solved examples and real life case studies"--